International Multi-Conference on Systems, Sygnals &Amp; Devices 2012
DOI: 10.1109/ssd.2012.6198101
|View full text |Cite
|
Sign up to set email alerts
|

Large-area wireless sensor system based on smart textiles

Abstract: The SensFloor® is a textile-based large-area sensor system which is installed beneath the floor. It is able to detect people moving across the floor, calculating their trajectories and distinguishes between foot steps and a fall. It enables a variety of different applications like control of automatic doors, intrusion alarm and activity monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Building elements such as walls and ceilings are more and more used for integrating (hidden) devices (Doctor, Iqbal, and Naguib 2014;Fernandez-Luque et al 2013;Grierson et al 2011;Helal et al 2012;Jimenez et al 2013;Lauterbach, Steinhage, and Techmer 2012;Mowafey and Gardner 2012;Olivier et al 2009;Raad and Yang 2009;Xian 2007) such as Internet protocol video cameras (Olivier et al 2009) and passive system antennas (Chan et al 2008), or as an interface to communicate with the inhabitants (Olivier et al 2009;Maier and Kempter 2009), for example, colour code display when an anomaly is detected (Romero et al 2009) and multitouch wall (Leusmann et al 2011).…”
Section: Necessary Evaluation Of the Building Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Building elements such as walls and ceilings are more and more used for integrating (hidden) devices (Doctor, Iqbal, and Naguib 2014;Fernandez-Luque et al 2013;Grierson et al 2011;Helal et al 2012;Jimenez et al 2013;Lauterbach, Steinhage, and Techmer 2012;Mowafey and Gardner 2012;Olivier et al 2009;Raad and Yang 2009;Xian 2007) such as Internet protocol video cameras (Olivier et al 2009) and passive system antennas (Chan et al 2008), or as an interface to communicate with the inhabitants (Olivier et al 2009;Maier and Kempter 2009), for example, colour code display when an anomaly is detected (Romero et al 2009) and multitouch wall (Leusmann et al 2011).…”
Section: Necessary Evaluation Of the Building Environmentmentioning
confidence: 99%
“…Intelligent floors (Lee et al 2009;Lauterbach et al 2012;Rowe et al 2009) have received substantial attention during the last decade for detecting fall, for providing gait monitoring, for location tracking, or for detecting presence and/or activity. They may be instrumented with accelerometers (Li 2013), piezoelectric sensors (Alwan 2009;Klack et al 2011;Leusmann et al 2011), (capacitive) pressure sensors (Olivier et al 2009;Helal et al 2012;Hoey et al 2011;Stefanov, Bien, and Bang 2004), micro-electro-mechanical systems (MEMS) (Fernandez-Luque et al 2013;Helal et al 2012), or innovative sensors using the near-field imaging principle (reported in Leone, Diraco, and Siciliano 2013), but the solution of a ready-to-be-used pressure-sensitive textile layer (Hanson, Barth, and Silverman 2011;Lauterbach et al 2012), called a presence mat or pressure mat, has been popular since the last years .…”
Section: Necessary Evaluation Of the Building Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…SensFloor is a textile-based large-area sensor system comprised of an underlay with embedded microelectronic modules, which can be seamlessly installed underneath the floor [2] [1]. Using capacitance proximity sensing, as opposed to pressure sensitive floors [3][5], allows for its installation beneath both soft (i.e.…”
Section: Sensfloormentioning
confidence: 99%
“…In this paper, we show how we use SensFloor [1], a textilebased large-area sensor system, comprised of a grid of capacitive sensor plates under the floor, for human localization and tracking. The sensor system does not allow for a natural user identification (as in [3]), however, the capacitive measurement approach provides more flexibility when it comes to the floor covering.…”
Section: Introductionmentioning
confidence: 99%